The Effect Of Workload And Job Stress On Job Satisfaction Through Burnout As A Mediation Variable In The Labor Department In Banten Province - Selly Lintari; Uli Wildan Nuryanto; Khaeruman Khaeruman (Amkop Management Accounting Review (AMAR), 2026)
Employees in government institutions play a crucial role in providing quality public services. However, heavy workloads, job-related pressures, and uncomfortable working conditions can lead to stress, burnout, and reduced job satisfaction. This study aims to examine the effect of workload and work-related stress on job satisfaction, both directly and indirectly through burnout as a mediating variable. This research employs a quantitative survey method. Data were collected from 100 employees at the Manpower Offices in Serang City, Serang Regency, and Cilegon City using a questionnaire. The analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) with SmartPLS software version 4.1.1.4. The results indicate that workload and work-related stress have a positive and significant effect on burnout. Burnout, in turn, has a negative and significant effect on job satisfaction and serves as a mediating variable between workload, work-related stress, and job satisfaction. The study concludes by emphasizing the importance of managing workload in a balanced manner, creating a comfortable work environment, and implementing burnout prevention programs to enhance employee job satisfaction.